PENGARUH RELIGIUSITAS DAN LOVE OF MONEY TERHADAP KEPATUHAN CALON WAJIB PAJAK - Ratnawardhani, Eki Andika; Ernawati, Widi Dwi; Fatimah, Annisa (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2020)
The purpose of this study was to determine the effect of religiosity and Love of money on prospective taxpayer compliance. Population of this research was students at State Universities in Malang and the amount sample is 393  respondent that was obtained by using  using purposive dan snowball sampling teqnique. The type of  research is quantitative method using the associative causal method. Data coolestion is done by distributing questionnaries  online and off line. The data analysis technique used in this study is multiple linear analysis. The results showed that the calculated value of t on the religiosity variable was 7,593, and the Love of money of 3,570 was greater than t table of 1,966. So religiosity and Love of money affect the compliance of prospective taxpayers. The variable that can explain the independent variable is 15.8%, and the remaining 84.2% is influenced by other variables not explained in this study.